2012
DOI: 10.3389/fmicb.2012.00139
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of Antibiotic Resistance Genes by Dairy Calves Fed Milk Replacers with Varying Doses of Antibiotics

Abstract: Elevated levels of antibiotic resistance genes (ARGs) in soil and water have been linked to livestock farms and in some cases feed antibiotics may select for antibiotic resistant gut microbiota. The purpose of this study was to examine the establishment of ARGs in the feces of calves receiving milk replacer containing no antibiotics versus subtherapeutic or therapeutic doses of tetracycline and neomycin. The effect of antibiotics on calf health was also of interest. Twenty-eight male and female dairy calves we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 57 publications
4
53
0
Order By: Relevance
“…Best management practices, such as low animal density and improved nutritional programs, can be developed and adopted to control infectious diseases on farms. In a recent study of antibiotic amendment in dairy calf milk replacer, subtherapeutic antibiotics provided no additional health benefit when the calves were provided a high level of nutrition (Thames et al 2012). In contrast, Quigley and Drew (2000) observed that calves experienced greater incidence of illness when antibiotics were not supplemented, but the calves in their study received a reduced nutritional intake.…”
Section: Issues and Recommendationsmentioning
confidence: 99%
“…Best management practices, such as low animal density and improved nutritional programs, can be developed and adopted to control infectious diseases on farms. In a recent study of antibiotic amendment in dairy calf milk replacer, subtherapeutic antibiotics provided no additional health benefit when the calves were provided a high level of nutrition (Thames et al 2012). In contrast, Quigley and Drew (2000) observed that calves experienced greater incidence of illness when antibiotics were not supplemented, but the calves in their study received a reduced nutritional intake.…”
Section: Issues and Recommendationsmentioning
confidence: 99%
“…With regards to aminoglycoside use in the Brazilian geographical regions from where the cheese samples were manufactured and acquired, no information was retrieved. Cattle farming is associated with a reservoir for potentially pathogenic and drug‐resistant bacteria or even a reservoir of antibiotic resistance genetic markers (Munir and Xagoraraki ; Thames and others ). In general, antimicrobial drugs are widely applied in animal husbandry in an attempt to increase production, related to prophylaxis, infectious disease treatment and/or growth promoters (Heuer and others ).…”
Section: Resultsmentioning
confidence: 99%
“…This approach has also provided strong evidence for an increased prevalence in antibiotic resistance associated with agricultural antibiotic use (e.g., Jindal et al, 2006;Peak et al, 2007;Zhou et al, 2009;McKinney et al, 2010). Limitations associated with this approach include variations across agricultural practices that can make it difficult to isolate the specific variable of antibiotic use, evidence that antibiotics (Zhou et al, 2009) and antibiotic-resistant bacteria may be present in the absence of use (Thames et al, 2012), and therapeutic antibiotic use for ill animals on organic farms (McKinney et al, 2010).…”
Section: Background and Controlsmentioning
confidence: 99%